2020
DOI: 10.1021/acs.jchemed.0c00748
|View full text |Cite
|
Sign up to set email alerts
|

Online Experimentation during COVID-19 Secondary School Closures: Teaching Methods and Student Perceptions

Abstract: The COVID-19 lockout situation affected people all over the world. Despite all of the disadvantages, this situation offered new experiences and perspectives and pushed education advances forward as never before. Something that seemed to be unreal became a worldwide reality within a few days. Instructors of all subjects at all educational levels moved to a virtual environment instantly. Higher education institutions, universities, and colleges seemed to be fairly prepared for this situation. Unfortunately, prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 28 publications
(32 reference statements)
3
56
0
7
Order By: Relevance
“…Unlike this finding, a study conducted by Abuhassna et al (2020) has reported that students had highly satisfied with online teaching. To consider the overall level of satisfaction with online teaching, several studies have been found in line with the findings of the present study (Aristovnik et al, 2020;Babinčáková & Bernard, 2020;Bauk et al, 2014;Bokayev et al, 2021;Bolliger & Wasilik, 2009;Chen et al, 2020;Durak, 2020;Fatani, 2020 2020; Mahdy, 2020bMahdy, , 2020aMalkawi et al, 2021;Nguyen, 2016;Di Pietro et al, 2020;Shahzadi & Ahmad, 2011;Sharma et al, 2020;Surahman & Sulthoni, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Unlike this finding, a study conducted by Abuhassna et al (2020) has reported that students had highly satisfied with online teaching. To consider the overall level of satisfaction with online teaching, several studies have been found in line with the findings of the present study (Aristovnik et al, 2020;Babinčáková & Bernard, 2020;Bauk et al, 2014;Bokayev et al, 2021;Bolliger & Wasilik, 2009;Chen et al, 2020;Durak, 2020;Fatani, 2020 2020; Mahdy, 2020bMahdy, , 2020aMalkawi et al, 2021;Nguyen, 2016;Di Pietro et al, 2020;Shahzadi & Ahmad, 2011;Sharma et al, 2020;Surahman & Sulthoni, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…In 2020, usage statistics of August and September compared to June and July month may be attributed to the usage of virtual laboratories in the curriculum for conducting online laboratory education in Indian universities. With the plethora of challenges facing in education sector post COVID-19, similar studies were also reported on transformation of traditional classes to online delivery considering potential impacts on learning experiences on student communities (Babinčáková & Bernard, 2020 ; Gamage et al, 2020 ).…”
Section: Discussionmentioning
confidence: 90%
“…The student found experimenting more motivating and fun and social in terms of learning the concepts better, and they claimed that not being able to experiment was the biggest deficiency. Babinčáková & Bernard (2020) determined in their study on online chemistry experiments with students that students found these activities instructive. On the other hand, another point that students criticize in distance education is that teaching is carried out with teacher-centered questions and answers and traditional approaches are mostly used (Koçoğlu & Tekdal, 2020).…”
Section: Introductionmentioning
confidence: 99%